Visualization of Freezing Process in situ upon Cooling and Warming of Aqueous Solutions - Bogdan, Anatoli; Molina, Mario J.; Tenhu, Heikki; Bertel, Erminald; Bogdan, Natalia; Loerting, Thomas (Scientific Reports, 2016)
Peer reviewed